ANALYSIS OF HEMATOLOGICAL PROFILES IN TUBERCULOSIS PATIENTS IN THE WORKING AREA OF THE KENDARI CITY HEALTH SERVICE - Usman, Julianti Isma Sari; Hasan, Aswiro; musrifah, Sari; Fauzi, Ahmad Zil (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2024)
Background: Pulmonary tuberculosis is still one of the main health problems in the world. Treatment of TB cases is one of the main strategies for controlling TB because it can break the chain of transmission. Anti-tuberculosis drugs can kill and inhibit Mycobacterium tuberculosis bacteria, but the use of these drugs can have side effects on different organs, especially the hematological system. Aims: This study aims to determine the hematological profile of tuberculosis patients undergoing treatment. Methods: The type of research used is descriptive quantitative with a cross-sectional approach. The independent variable is pulmonary TB patients undergoing treatment, the dependent variable is the hematological profile with a sample of 70 tuberculosis patients whose specimens were taken in the form of venous blood with K3EDTA anticoagulant. The results: frequency of anemia in male TB 32 people and female 14 people, followed by a decrease in hemoglobin levels, hematocrit and erythrocyte count. The absolute value of the erythrocyte index in tuberculosis patients was found to be a normal MCV value (77%) and decreased by 23%. MCH values were normal in tuberculosis patients (89%) and 11% experienced a decrease. For MCHC and RDW CV, it was found that there was an increase in values above the reference values, however, TB patients (83%) had normal MCHC values and 17% had increased MCHC values. Likewise, 87% of RDW CV had normal RDW CV values and 13% of tuberculosis patients had increased RDW CV values. The erythrocyte sedimentation rate in TB patients increased in men by 63% and women by 50%. Conclusions: TB patients undergoing treatment have normal leukocyte and platelet counts. From the results of leukocyte examination, 85% of patients had normal leukocyte counts, 12% leukocytosis and 3% leukopenia. The number of platelets in tuberculosis patients is 93% normal, 1% thrombocytopenia and 6% thrombocytosis.Keywords: Hematology, Tuberculosis Patients, Pulmonary TB